2019
DOI: 10.1103/physrevb.100.220406
|View full text |Cite
|
Sign up to set email alerts
|

BiMnTeO6 : A multiaxis Ising antiferromagnet

Abstract: The crystal and magnetic properties of honeycomb BiMnTeO 6 have been studied between 1.5 K and 300 K using synchrotron X-rays and neutron scattering experiments. Commensurate magnetic ordering is observed below T N = 10 K, and corresponds to a non collinear spin arrangement, with spins tilted away from the anisotropy easy-axis set by the Jahn-Teller distortion of the MnO 6 octahedra. Inelastic scattering experiments show two main nearly localised magnetic excitations, which can be well described by an exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…As the collision cascades become less dilute due to the large ion mass, more of these intrinsic defects survive and bind to C N , explaining the ion mass dependence. In addition, the role of C interstitials (C i ) cannot be neglected: Matsubara and Bellotti [38] have shown that the C N C i complex has a similar energy position in the bandgap to that of C N alone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the collision cascades become less dilute due to the large ion mass, more of these intrinsic defects survive and bind to C N , explaining the ion mass dependence. In addition, the role of C interstitials (C i ) cannot be neglected: Matsubara and Bellotti [38] have shown that the C N C i complex has a similar energy position in the bandgap to that of C N alone.…”
Section: Resultsmentioning
confidence: 99%
“…[13] In addition, since A1 is detected irrespective of the implanted species, it is more likely that it has an intrinsic nature. Impurities might also play a role: According to theoretical studies performed by Matsubara and Bellotti, [38] the microscopic nature of this level can be linked to either positive charge state of C N or C N Si Ga . [39] Yet the former possibility can be ruled out because, if that were the case, both H1 and A1 would have the same concentrations, which is not the case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Layered oxides have attracted considerable attention over the last decades owing to their intriguing physical and chemical properties across a wide scope of science, including, phase transitions (e.g. antiferromagnetism, superconductivity, Kitaev magnet) 2 5 , thermodynamics (e.g. fast ionic conductivity) 6 and unusual electromagnetic spin interactions (multiferroics, high-voltage electrochemistry) 7 – 9 .…”
Section: Introductionmentioning
confidence: 99%